(3GdCeGdj GdfMhjIs - (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS GdeGdcj GdcQOj GdCSfGFj GdeUQj , CHh YeQh LeGd GdOjf GHf GdMGLH , J (B646 (3g` s
(3ChdgG (B:s
(3bGd GdTjN Hf GdMGLH JbGJdhfge Ch jSdehf ddQaY hLgGf CMOgeG s
(3BNQgG (B:s
(3hGdKGfi EQGOI GdGNJUGQ eeG de jcKQ HNdGa GdeaQO GdeLehY aGZJaQ GddHS ai Gdbdjd GdGNJUGQ hGddg CYde HGdUhGH s
(3CJHY GdfGSN GdeNWhWI HaGFOI fMhjI dGHf GdMGLHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI HgG JdhjK s
Keywords: (3GdfMhs